Integrated mine planning system for a sustainability of mining business (Case study: X coal mine project) - WAHYU SUMARSIDI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: Even though the project has been declared run based on the feasibility analysis results, this study assessed the mining company’s operations as prices began to drop. The POAC approach will be used throughout observing the parameter mentioned above, from planning and organisation to actuation and control.Method: Due to the positive results of the feasibility study, the project is now considered operational, and this study examined how the mining industry operates in the face of falling prices. Starting with scheduling and moving on to coordination, actuation, and management, the POAC method was used to keep the parameter under control.Findings: The results predicted that although the project has been declared to be feasibly run, it is still possible and should to re-conduct a feasibility study or planning strategy due to the changes in parameters, both technical and economic parameters, which are assumed as the basis for making plans and its makes the plan remains relevant. To remain profitable, a mining company needs to adjust to new circumstances quickly and easily, no matter how dire they may get.Implications/Novel Contribution: Comprehensive information about mine planning has been compiled as a result of this study. The findings may aid policymakers in better comprehending the system, which may lead to greater efficacy.